FACE RECOGNITION WITH ILLUMINATION VARYING CONDITIONS AND OCCLUSIONS - Algharib, Amal M; Baba, Abdellatif (MATTER: International Journal of Science and Technology, 2016)
Face recognition with illumination varying conditions and occlusions is one of the most important challenges in the field of digital image processing. Despite of the fact that a number of studies (Patel & Yagni, 2013; Azeem, Sharif, Raza & Murtaza, 2014) have improved the accuracy of different techniques by normalizing and compensating the illumination variations using some pre-processing methods, a lot of these methods are still facing many serious challenges with illumination changes and occlusion. In this paper, we suggest the use of tow pre-processing methods that will have a great impact on the performance and the robustness of the recognition procedures in case small sample size (SSS) as the training set.